Android-based STEM-AR and its contribution to elementary school students' environmental literacy - Nasaruddin, Datuk Muhammad; Maryani, Ika; Sanjun, Cindy Joe; Sulisworo, Dwi; Widyaningrum, Trianik; Santosa, Achadi Budi (International Journal of Education and Learning, 2025)
This study is motivated by the low environmental literacy and academic achievement of elementary school students. The study aims to measure the effect of Android-based STEM-AR on students' environmental literacy. A quantitative research method with a One Group Pretest-Posttest Design was used. A total of 31 fifth-grade elementary school students in Yogyakarta, Indonesia, were randomly selected from nine public schools. The research instruments included a lesson plan and an Augmented Reality (AR) medium accessible via Android smartphones. STEM was used as a reference for structuring subject matter. The treatment was conducted four times, each lasting 70 minutes. Students' environmental literacy was measured before and after the treatment using a validated multiple-choice test. Data analysis employed a t-test with a 5% significance level. The Paired Sample Test results showed a sig(2-tailed) value of 0.001 0.05, which led to the rejection of the null hypothesis and acceptance of the alternative hypothesis. This study contributes to proving that Android-based STEM-AR positively influences elementary school students' environmental literacy.